PEMBERDAYAAN KELOMPOK WANITA TANI (KWT) NAGARI SIPANGKUR DALAM PEMBUATAN KOMPOS DARI LIMBAH PERKEBUNAN KELAPA SAWIT - Sari, Wulan Kumala; Ifmalinda, Ifmalinda; Ediset, Ediset; Srilanang, Suai Namun; Ansharullah, Aziz; Nelty, Hanny Nadhila; Hutahuruk, Santa Brightness; Mizan, Irfathil; Yustika, Wildan Zikrillah (Jurnal Abdi Insani, 2025)
Oil palm as the plantation commodities that economically promising, has encouraged extensification, such as in Dharmasraya, Tiumang District, Sipangkur Village. The Tunas Jaya Women Farmers Group (WFG) in Sipangkur Village has been formed since 2019, but its role and function still on a household scale and not optimal in managing oil palm plantation waste due to lack of knowledge and technology. The objective of this community service was to empower the Tunas Jaya WFG to optimize the existence of oil palm plantations, by managing oil palm plantation waste to be as organic fertilizer (compost). This community empowerment began with dissemination, counseling, followed by demonstrations and assistance in making compost from oil palm fronds and empty oil palm bunches (EFBs). Furthermore, monitoring and evaluation are carried out for 3 months after it. During the dissemination, participants actively discussed about the proper composting techniques. The response and enthusiasm of them showed that this program had succeeded in increasing their curiosity about the importance of managing oil palm plantation waste to have added value. During the demonstration and assistance activities for making compost, the farmer groups were assisted and guided by the community service team, such as in the chopping of fronds and EFBs. Application of the proper composting technique will provide of effectiveness and efficiency of resources. In addition, compost can be a substitute of synthetic/chemical fertilizers and supports the ecosystem sustainability. The enthusiasm of the farmer groups and the community, as well as the successful of independent compost production are evidence and indicators of the successful of this community service activity.